OPTIMALISASI TRANSAKSI NON-MONETER MELALUI PERANCANGAN MARKETPLACE BARTER BARANG DAN JASA - Hayaza, Ahmad Taufik Hayaza; Kharenina Rizqy Putri Nugroho; Ima Muhimmah Falasifa; Farel Fazriel Marbella; Abdul Rezha Efrat Najaf; Muhammad Reza Pahlawan (Prosiding Seminar Nasional Teknologi dan Sistem Informasi, 2026)
Contemporary digital transformation necessitates adaptive fulfillment models to mitigate the discrepancy between domestic asset ownership and limited cash liquidity. The fundamental issue lies in the accumulation of usable commodities undergoing utility value depreciation due to the lack of efficient and credible exchange mechanisms. This research aims to develop a mobile-based barter marketplace application as a systematic instrument for non-monetary value exchange. The development methodology adopts the Scrum framework with a Minimum Viable Product (MVP) orientation to ensure functional system resilience through sprint cycles. System innovations include integrated entity categorization by typology and weight dimensions, which automatically formulate location-proximity-based exchange recommendations to optimize distribution logistics. Additionally, exchange target specification features are implemented to enhance transaction accuracy according to detailed user preferences. Research findings indicate that the platform effectively mediates equivalent value exchange through a hybrid barter mechanism, where asset value disparities are compensated by service provision. This study concludes that the digitalization of the barter system serves as a catalyst for inclusive circular economy empowerment and a strategic solution for fulfillment independent of monetary dependency.